Milk fat globule membrane supplementation protects against β-lactoglobulin-induced food allergy in mice via upregulation of regulatory T cells and enhancement of intestinal barrier in a microbiota-derived short-chain fatty acids manner - Han Gong; Tiange Li; Dong Liang; Jingxin Gao; Xiaohan Liu; Xueying Mao (Food Science and Human Wellness)
Milk fat globule membrane (MFGM), which contains abundant glycoproteins and phospholipids, exerts beneficial effects on intestinal health and immunomodulation. The aim of this study was to evaluate the protective effects and possible underlying mechanisms of MFGM on cow’s milk allergy (CMA) in a β-lactoglobulin (BLG)-induced allergic mice model. MFGM was supplemented to allergic mice induced by BLG at a dose of 400 mg/kg body weight. Results demonstrated that MFGM alleviated food allergy symptoms, decreased serum levels of lipopolysaccharide, pro-inflammatory cytokines, immunoglobulin (Ig) E, IgG1, and Th2 cytokines including interleukin (IL)-4, while increased serum levels of Th1 cytokines including interferon-γ and regulatory T cells (Tregs) cytokines including IL-10 and transforming growth factor-β. MFGM modulated gut microbiota and enhanced intestinal barrier of BLG-allergic mice, as evidenced by decreased relative abundance of Desulfobacterota, Rikenellaceae, Lachnospiraceae, and Desulfovibrionaceae, while increased relative abundance of Bacteroidetes, Lactobacillaceae and Muribaculaceae, and enhanced expressions of tight junction proteins including Occludin, Claudin-1 and zonula occludens-1. Furthermore, MFGM increased fecal short-chain fatty acids (SCFAs) levels, which elevated G protein-coupled receptor (GPR) 43 and GPR109A expressions. The increased expressions of GPR43 and GPR109A induced CD103+ dendritic cells accumulation and promoted Tregs differentiation in mesenteric lymph node to a certain extent. In summary, MFGM alleviated CMA in a BLG-induced allergic mice model through enhancing intestinal barrier and promoting Tregs differentiation, which may be correlated with SCFAs-mediated activation of GPRs. These findings suggest that MFGM may be useful as a promising functional ingredient against CMA.